Sesbania sesban as a fodder tree in Ethiopian livestock farming systems: Feeding practices and farmers' perception of feeding effects on sheep performance - Oosting, Simon J.; Mekoya, A.; Fernández Rivera, S.; Zijpp, A.J. van der (Elsevier, 2011)
Sesbania sesban is one of the exotic multipurpose fodder trees introduced in the Ethiopian highlands for livestock feed and soil conservation. Several on-station studies showed that supplementation with Sesbania improved intake and digestibility of basal diet and growth rate of animals. However, information about farmers' feeding practices of Sesbania and farmers' perception of the effect of Sesbania feeding on animal performance is limited. The present study was conducted to assess farmers' feeding practices and their perception about effects of Sesbania supplementation on sheep performance in annual (one wheat-based (WheatCL) and one teff-based (TeffCL)) and perennial (coffee-based (CoffeeCL)) crop-based livestock systems in the Ethiopian Highlands. Data were collected from 98 households by interviews using a structured questionnaire. Farmers had on average 6.9 years of experience using Sesbania as a cut and carry supplementary feed. Farmers in the WheatCL and TeffCL fed Sesbania throughout the dry season while farmers in the CoffeeCL had no specific season for feeding Sesbania. Farmers in WheatCL and TeffCL offered significantly (P < 0.05) more frequently and a higher quantity per feeding of Sesbania than farmers in CoffeeCL. Most farmers perceived increased lamb birth weight and increased body weight gain, earlier onset of puberty, and improved pregnancy rate of ewes and rams' libido. Perceived improvement was significantly more (P < 0.05) in WheatCL and TeffCL than in CoffeeCL. We concluded that Sesbania was appreciated across farming systems for its feeding value. The marginal advantage of Sesbania was lowest in the CoffeeCL with relatively good availability of good quality feeds compared to the WheatCL and TeffCL, which explains the less positive perception of production and reproductive performance of Sesbania feeding in CoffeeCL.